MAIN DIRECTIONS OF EFFICIENCY IMPROVEMENT OF TRANSPORT INTERCHANGES FUNCTIONING - Naumov, V.; Samchuk, A.; Наумов, В. С.; Самчук, А. А.; Самчук, Г. О. (Харьковский национальный автомобильно-дорожный университет, 2015)
The article deals with the areas of study concerning transport interchanges. It has been determined that the most perspective directions for the future research is synchronization of the schedule that allous reducing the wating time, preventing the public transport congestion at bus stops and stations, and by doing this to ensure their sustainable development.
ОСНОВНЫЕ НАПРАВЛЕНИЯ ПОВЫШЕНИЯ ЭФФЕКТИВНОСТИ ФУНКЦИОНИРОВАНИЯ ТРАНСПОРТНО-ПЕРЕСАДОЧНЫХ УЗЛОВ
ОСНОВНІ НАПРЯМИ ПІДВИЩЕННЯ ЕФЕКТИВНОСТІ ФУНКЦІОНУВАННЯ ТРАНСПОРТНО-ПЕРЕСАДОЧНИХ ВУЗЛІВ
Keywords: transport interchange; efficiency; sustainable development; synchronization; транспортно-пересадочный узел; эффективность; устойчивое развитие; синхронизация; транспортно-пересадочний вузол; ефективність; сталий розвиток; синхронізація; 656.025.2=111